Identifying Priorities for Marine Tourism Development at Tanggamus Regency, Lampung - Annishia, Fristi Bellia (Jurnal Penelitian Pariwisata, 2021)
This research aims to determine priorities for the development of marine tourism in Tanggamus Regency. To obtain recommendation for priority for marine tourism development, this research focuses on three marine tourism destinations that managed by Tourism Awareness Group (Pokdarwis) together with Tanggamus Government, namely Kiluan Bay, Karang Putih Beach, and Muara Indah Tourism Park. Focus Group Discussions (FGD) as well as questionnaire were conducted with informants from Tourism, Culture, Youth and Sports Agency of Tanggamus Regency, and Pokdarwis representatives from management of the research location. This research uses Analytical Hierarchy Process (AHP) method, and the priority preferences for the development of marine tourism are assessed from the aspects of connectivity (C1), governments program support (C2), potential problems (C3), and potential value-added locations (C4). The results show indicators in each data cluster prioritize Kiluan Bay as the first priority to be developed. The results also recommend to increase tourism promotions in the airport area and optimizing the constructions of access roads (C1), synchronizing tourism development plans in the Regional Spatial Plan to the Lampung Province Medium-Long Term Development Plan and facilitating investors in the tourism sectors (C2), educating the public regarded the potential dangers of disasters (C3), supporting for accommodations, local communities attractions and culinary centers (C4). Keywords: Analytical Hierarchy Process, Marine Tourism, Priorities of Development.